Penguasaan Kompetensi Digital Berdasarkan Efikasi Diri Dan Jenis Kelamin: Tinjauan Literatur Sistematis - Saputri, Rizky Novia; Prasetiyo, Wibowo Heru (Jurnal Civic Hukum, 2023)
The progress of the digital era has become increasingly rapid in recent years, including its impact on the world of education which must prepare competent human resources. Students are expected to have competencies that can meet the demands of the times. This research aims to identify the relationship between men's and women's self-efficacy towards their mastery of digital competencies. Using Systematic Literature Review (SLR), guided by the PRISMA review protocol using three databases, namely Scopus, Doaj and Eric, related to digital competence, self-efficacy and socio-demographic gender. In this study, 265 articles were screened, then 20 articles were obtained that met the predetermined inclusion and exclusion criteria. After that it is filtered with open journal access options and some restrictions. The results of this systematic literature survey show that the self-efficiency of digital competence between men and women is equal. Self-effectiveness of digital competencies plays a key role in student learning performance as it greatly affects student confidence in problem-solving, interpreting and understanding digital learning materials and performing well in digital learning.